Heavy Oil Potentials in Central Sumatra Basin, Indonesia Using Remote Sensing, Gravity, and Petrophysics Data: From Literature Review to Interpretations and Analyses - Tri Muji Susantoro; S. Suliantara; Herru Lastiadi Setiawan; Bambang Widarsono; Ketut Wikantika (Universitas Pendidikan Indonesia, 2022)
Central Sumatra basin is located on Sumatra Island, Indonesia, and is considered an oil prolific basin that produces heavy oil. The basin is believed to have unexplored heavy oil potential. Therefore, this study aims to map the heavy oil potential distribution in the basin using surface and subsurface lineaments analyses interpreted from satellite imagery and gravity data, and assisted by well log/petrophysics analysis. A thorough basin analysis was conducted based on surface/subsurface structures’ control and source rock location settings to map all potential heavy oil traps. The gravity anomaly data interpretation identified the low areas and lineaments in NW – SE, and N – S directions. The interpretation of satellite imageries showed very similar lineament patterns with the same general direction. It was observed that there is continuity between subsurface and surface lineament features, which provide contact between reservoirs and surface water sources, thereby facilitating heavy oil generation. Overlapping the lineament interpretation of gravity and satellite imagery data, supported by petroleum system understanding and verification from wells data have confirmed 7 heavy oil trap potential areas within the sedimentary basin.